Electrolyte Stability and Discharge Products of an Ionic-Liquid-Based Li-O-2 Battery Revealed by Soft X-Ray Emission Spectroscopy - Leon, Aline; Fiedler, Andy; Blum, Monika; Yang, Wanli; Bär, Marcus; Scheiba, Frieder; Ehrenberg, Helmut; Heske, Clemens; Weinhardt, Lothar (Journal of Physical Chemistry C, 2019)
We investigate the electrolyte stability and discharge products of an ionic-liquid-based Li-O-2 battery through soft X-ray emission spectroscopy (XES) experiments, which offer unique site specificity for detecting subtle changes in the local nitrogen and oxygen environment. We benchmark the valence electronic structures of the molecules composing the electrolyte, namely the solvent PP13(TFSI), the salt LiTFSI, and the PP13 cation. Then, the transformation of the electrolyte is shown using cathodes stopped at different discharge and charge stages. We provide experimental evidence that the nitrogen site of the salt is unstable during electrochemical operation. The chemical environment of the nitrogen atoms is gradually changed during the electrochemical cycle, indicating the breaking of S-N bonds. The ionic liquid solvent remains mostly as an ion pair, but some decomposition into PP13 cations and TFSI anions cannot be ruled out. Our results and detailed analysis also show that the discharge products in our cell consist of lithium peroxide with some amount of hydroxide; however, no carbonate is observed.
CRIS-Team WoS Importer:2020-01-24